Experiments With Plasmas Artificially Injected Into Near-Earth Space - Haerendel, Gerhard (Frontiers in Astronomy and Space Sciences, 2019)
Plasma injection experiments in space are being ordered according to five aspects: (1) Diagnostics of electric fields, (2) Coupling to the ionosphere, (3) Interactions with the solar wind, (4) Modification experiments, and (5) Special physical processes. Historically first were releases of neutral gases with the aim to measure atmospheric parameters. They were soon followed by plasma injections applied to the measurement of plasma flows and parallel electric fields. Long-range coupling to the environment was a most important aspect of the plasma releases. It concerned, on the one hand, the need for corrections of the derived diagnostic parameters and, on the other hand, the understanding of the formation of the ubiquitous striations and deformations of the plasma clouds. A special application was the investigation of cometary interactions by releases in the solar wind. Modification experiments in the ionosphere were done intentionally or occurred as byproducts of rocket launches or other activities. A particular goal was to trigger natural large-scale ionospheric instabilities like equatorial spread F in order to improve the understanding of the natural phenomena. Large-scale plasma injections in the magnetosphere have been performed in order to change the conditions of wave-particle interactions and potentially trigger observable effects. Special goals were so-called skidding experiments and testing Alfvén’s critical ionization velocity effect. In this review we will emphasize the principle objectives and illustrate the results from selected experiments.